(untitled) (Research, Society and Development, 2021)
The objective was to carry out an analysis of the handling of milking carried out in rural properties that use milk for subsistence, seeking to highlight risk factors and thereby contribute to improving this practice and the quality of milk consumed in rural properties located in the municipality of Uruguaiana, Rio Grande do Sul. To conduct the study, 10 farms were selected where beef cattle and sheep are raised in the extensive system and which have dairy or crossbred cows intended for milking to obtain milk for human consumption. the resort. After the selection, a semi-structured guide questionnaire was given to each owner to obtain information regarding handling during milking and the milk obtained. At the end of the interview, each response from each property was considered a variable. The data obtained were tabulated in Excel, studied descriptively as to the occurrence percentages and analyzed with the help of IBM SPSS Statistics 20.0 software. From the analysis it was found that manual milking is performed in most of the properties and in a location not appropriate for this purpose. Regarding the care with milk hygiene and the health of the cows, it was found that they are below the desired in all properties. Thus, from this knowledge it is possible to carry out actions aimed at improving the quality of milk, aiming to preserve the health of the people who consume this product, as well as its by-products.